Human Rights Aspects of the Acquisition of Agricultural Lands With Special Regard to the ECtHR Practice Concerning the So-Called “Visegrád Countries”, Romania, Slovenia, Croatia, and Serbia - Marinkás, György (Acquisition of Agricultural Lands, 2022)
The aim of the current study is to examine how the national legal rules and judicial practice regarding the acquisition and holding of agricultural land are, in the case law of the European Court of Human Rights, linked to the right to property and the right to fair trial, as granted by Article 1 of the First Protocol to the European Convention on Human Rights and Article 6 (1) of the Convention. The study is focused on the land-related issues of the so-called “Visegrád Countries”—Czech Republic, Hungary, Poland and Slovakia—and some other selected neighboring countries, namely Romania, Slovenia, Croatia, and Serbia, all of which are member states of the Council of Europe. The author identified two main categories of legal issues, which are relevant in the selected countries or constitute a distinctive feature of these countries. The category of compensation-related cases can be divided into three main subcategories: cases where the compensation system established by the state after the change of regime displayed systematic shortcomings; cases where the earlier proprietors’ or their heirs’ interests clashed with those of third parties who acquired the property in good faith; and the so-called Slovakian “Gardener cases,” as the author named them, which display similarities with the second subcategory. The other main category is the issue of agricultural land acquisition by foreign natural or legal persons. However, the ECtHR’s case law is not that elaborated in this question as the case law of the Court of Justice of the European Union, since, contrary to EU law—which as a rule obliges member states to provide the free disposal of agriculture land—Article 1 of Protocol No. 1 does not create a right to acquire property. However, a national legislation that, alone among the CoE member states, implemented land reform programs with some blanket restrictions on the sale of agricultural land is incompatible with the provisions of Article 1 of Protocol No. 1. Keywords: agricultural land, right to property, compensation, legal entity, foreigners